2021
DOI: 10.1002/joc.7329
|View full text |Cite
|
Sign up to set email alerts
|

Trends in probabilities of temperature records in the non‐stationary climate of South Africa

Abstract: The temporal and spatial distribution of the frequency of breaking highest and lowest daily maximum and minimum temperature records over the period of 1951–2019 has been investigated for South Africa. Temperature records are station specific and defined as either larger or smaller than any previous values in a time series of specific year‐days. Daily maximum and minimum temperatures from homogenized time series of 25 weather stations in South Africa were analysed. Aspects considered to influence the frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…In these regions, extremes will continue to rise and reach unprecedented strengths in the future. This is true especially over continents and corresponds to the well-known fact that global warming is stronger over land than over the oceans or in coastal regions ([ 16 , 82 ]). However, we find a disagreement between the earth system models in terms of the total magnitude of the changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these regions, extremes will continue to rise and reach unprecedented strengths in the future. This is true especially over continents and corresponds to the well-known fact that global warming is stronger over land than over the oceans or in coastal regions ([ 16 , 82 ]). However, we find a disagreement between the earth system models in terms of the total magnitude of the changes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that changes in extreme temperature are not taking place uniformly around the globe, but that they are instead showing a strong dependency on the geographic location and its climatic conditions. This is visible already on a regional level ([ 16 , 17 ]) and even more globally ([ 18 ]). Earth system model simulations predict this variability also to be present in the future development of Earth’s climate ([ 19 , 20 ]).…”
Section: Introductionmentioning
confidence: 99%
“…To investigate any abrupt changes in the mean α and β -parameters the differences in these means before and after every year were tested, starting in 1951. By observing changes from a decrease to an increase in the absolute value of the Student's t-test one can identify abrupt changes in the means (McBride et al, 2021). Years of abrupt change in the mean αparameter were 1975 and 1995, while for the β -parameter it was 1974-1975 (Fig.…”
Section: Temporal Change In Extreme Value Distribution Parametersmentioning
confidence: 99%
“…Econometrically, the author suggests taking into account the non-stationarity of climate change, as is evident on the continent (Gosoniu et al 2009;Karambiri et al 2011;Djibo et al 2015;Garcia-Aristizabal et al 2015;De Paola et al 2018;McBride et al 2022). A reviewer of this manuscript highly recommended using variations from the mean for temperature and rainfall as key explanatory variables to capture the long-term variability of climate change.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%